Analysis of nasal potential in murine cystic fibrosis models. (November 2016) - da Cunha, Mélanie Faria; Simonin, Juliette; Sassi, Ali; Freund, Romain; Hatton, Aurélie; Cottart, Charles-Henry; Elganfoud, Nadia; Zoubairi, Rachid; Dragu, Corina; Jais, Jean Philippe; Hinzpeter, Alexandre; Edelman, Aleksander; et al.
Abstract: The nasal epithelium of the mouse closely mimics the bioelectrical phenotype of the human airways. Ion transport across the nasal epithelium induces a nasal transepithelial potential difference. Its measurement by a relatively non-invasive method adapted from humans allows in vivo longitudinal measurements of CFTR-dependent ionic transport in the murine nasal mucosa. This test offers a useful tool to assess CFTR function in preclinical studies for novel therapeutics modulating CFTR activity. Here we extensively review work done to assess transepithelial transport in the murine respiratory epithelium in the basal state and after administration of CFTR modulators. Factors of variability and discriminative threshold between the CF and the WT mice for different readouts are discussed.